Phospholipid multilamellar vesicles entrapping phenothiazine photosensitizers. Preparation, characterization and evaluation of their photodynamic properties - Vara, Jimena (2019)
The aim of the present paper was to optimize the properties of phenothiazine photosensitizers (PSs), Azure B and its monobrominated derivative. They were entrapped in multilamellar liposomes of egg phosphatidylcholine (EPC) and dipalmitoylphosphatidylcholine (dpPC). The higher partition coefficient of both PSs in the EPC/water system compared with that of both PSs in the dpPC/water system allowed the selection of EPC to be used for the development of third generation photosensitizers. The optimal phospholipid/phenothiazine ratio and the location of these dyes in the lipid bilayer systems were established. These dyes were found to be located within the polar head group region of the lipid bilayer, which would enhance the effectiveness of the irradiation procedure. In addition, the encapsulation of both photosensitizers in liposomes led to a decrease in the aggregation of these compounds, and consequently to an increase in their singlet oxygen quantum yield (ϕΔ). The encapsulation of the PSs in lipid vesicles significantly increased their photochemical reactivity, doubling the ϕΔ value of AzBBr and increasing that of AzB by 60%. The results obtained demonstrate that the vehiculization of these PSs in liposomes allowed the development of third generation photosensitizers with better photochemical properties to be used in potential therapeutic applications.